Antimicrobial activity of hippurate nanocomposite and its cytotoxicity effect in combination with cytarabine against HL-60 - Hussein Al Ali, Samer Hassan; Al-Qubaisi, Mothanna; El Zowalaty, Mohamed Ezzat; Hussein, Mohd. Zobir; Ismail, Maznah (Hindawi Publishing Corporation, 2013)
Hippuric acid (HA) was intercalated into a zinc-layered hydroxide (ZLH) by direct reaction of an aqueous suspension of zinc oxide with an aqueous solution of hippuric acid to obtain hippurate nanocomposite (HAN). Various concentrations of hippuric acid (0.05, 0.2, and 0.4 molar) were used for the synthesis of the nanocomposite. The as-synthesized HAN using 0.2 molar was found to give a well-ordered layered nanocomposite material with an increase in the basal spacing to 21.3 Å which indicated the insertion of hippurate organic moiety into the ZLH interlayers. The cytotoxicity of HAN in combination with cytarabine against human promyelocytic leukemia cells (HL-60) was tested using MTT cell viability assay and trypan blue dye exclusion assay. The combination of cytarabine with HAN showed higher tumor suppression efficiency as compared to that of cytarabine alone. The IC50 values of HAN/cytarabine combination and cytarabine alone were  μg/mL and  μg/mL, respectively. DNA fragmentation was also studied, and the exposure of HL-60 cells to cytarabine produced % DNA fragmentation compared to % when cells were exposed to combination of cytarabine with HAN. The antimicrobial activity of hippuric acid and HAN nanocomposite was carried out against Gram-positive bacteria, Gram-negative bacteria, and yeasts. It was found that Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus were more sensitive to HAN compared to Bacillus subtilis and Salmonella choleraesuis.